2017
DOI: 10.12691/education-5-10-13
|View full text |Cite
|
Sign up to set email alerts
|

Academic Self Concept and Academic Achievement of Secondary School Students

Abstract: At the level of secondary school, student's self-concept about their academic capabilities plays an important role. The aims of the study were to examine the relationship between academic self-concept and academic achievement of secondary students and to compare the academic self-concept of male and female secondary students. Sample of the study were 615 secondary school students of both genders (Male 317, Female 298, aged 14-17 years). The sample was drawn from 15 secondary schools affiliated with CBSE board,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 34 publications
3
25
1
5
Order By: Relevance
“…This means that the model-based group had gained a positive attitude about how good they are towards science. Several studies revealed (Jaiswal & Choudhuri, 2017;Jansen, Schroeders, & Lüdtke, 2014;Marsh & Martin; that the development of positive academic self-concept of students toward science is essential to boost their confidence in their ability to do well in science leading to academic achievement and optimize performance hence, it should be given much priority. In addition, students who have positive self-concept toward science tended to have higher aspirations in science (DeWitt et.…”
Section:  Results and Discussionmentioning
confidence: 99%
“…This means that the model-based group had gained a positive attitude about how good they are towards science. Several studies revealed (Jaiswal & Choudhuri, 2017;Jansen, Schroeders, & Lüdtke, 2014;Marsh & Martin; that the development of positive academic self-concept of students toward science is essential to boost their confidence in their ability to do well in science leading to academic achievement and optimize performance hence, it should be given much priority. In addition, students who have positive self-concept toward science tended to have higher aspirations in science (DeWitt et.…”
Section:  Results and Discussionmentioning
confidence: 99%
“…Consequently, adolescents were being highly confidence towards their study that reflects the academic self-concept. In addition, the academic selfconcept is associated with the academic achievement (Marsh & Martin, 2011;Jaiswal & Choudhri, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…En particular, se destaca la relación directa del autoconcepto académico y las calificaciones de los estudiantes, siendo esta variable la que tiene mayor peso en relación a todas las demás incorporadas al modelo. Este resultado está en línea con otras investigaciones que advierten que el autoconcepto académico sería una de las variables motivacionales con mayor influencia en el rendimiento escolar (Kumar & Choudhuri, 2017;Núñez et al, 1998;Ramos-Díaz, Rodríguez-Fernández, Ros & Antonio-Agirre, 2017). Así, cuando un sujeto se siente competente valora la tarea y favorece los sentimientos de autoeficacia y el control sobre su conducta, se sentiría responsable de sus aprendizajes evidenciando mejores resultados académicos (Morales, 2017;Núñez et al, 1998).…”
Section: Discusión Y Conclusionesunclassified
“…Un estudiante autopercibido como competente, valorará el desafío de la tarea y favorecerá sentimientos de autoeficacia y de control sobre su propia conducta, sintiéndose por tanto directamente responsable de sus logros y aprendizajes (Morales, 2017). En general, las investigaciones revelan una relación positiva entre autoconcepto académico y el logro académico (Chacón & Huertas, 2017;Kumar & Choudhuri, 2017). El autoconcepto tiene efectos positivos en la relación maestro-alumno, la relación con los compañeros, la participación en actividades y el clima escolar (Huang, Yu & Wu, 2019).…”
Section: Introductionunclassified